Lateral orbitofrontal cortex anticipates choices and integrates prior with current information - Ramon Nogueira (Nature Portfolio, 2017)
The orbitofrontal cortex encodes outcomes, expected rewards and values, but it is unclear how this region uses this information to inform action selection. Here, the authors show that lateral orbitofrontal cortex anticipates upcoming choices and combines recent prior information with current sensory information.